Prospects and Challenges of Asian Economic Integration: Lessons From European Union - Chauhan, Pradeep S. (Prabandhan: Indian Journal of Management, 2010)
The History of the formation on the European Union takes us back around 1951, with the formation of European Coal and Steel Community (ECSC) between France, West Germany, Belgium, Luxembourg and the Netherlands to pool the steel and coal resources of its member-states. This treaty was signed at Paris. This was a fulfillment of a plan developed by a French economist Jean Monnet, publicized by the French foreign minister Robert Schuman, which was also strongly supported by the United States. The "Treaty of Pars" entered in force by 1952 and was time limited to 50 years. This coalition was very important because steel had played an important part in arms production in World War II and was a fundamental resource of the western European states.